1998
DOI: 10.1083/jcb.142.1.251
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Outside-In and Inside-Out Signaling by Drosophila Neuroglian, a Member of the L1 Family of Cell Adhesion Molecules

Abstract: Expression of the Drosophila cell adhesion molecule neuroglian in S2 cells leads to cell aggregation and the intracellular recruitment of ankyrin to cell contact sites. We localized the region of neuroglian that interacts with ankyrin and investigated the mechanism that limits this interaction to cell contact sites. Yeast two-hybrid analysis and expression of neuroglian deletion constructs in S2 cells identified a conserved 36-amino acid sequence that is required for ankyrin binding. Mutation of a conserved ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 35 publications
4
66
0
Order By: Relevance
“…The Fas2 tumor invasion and blocked BC migration phenotypes indicate that Fas2 is both necessary and sufficient to inhibit invasion, and that its pattern of expression predicts epithelial invasion. (Goodman et al, 1997); Dlg-4.1 (Lue et al, 1996); Nrg-Ank (Hortsch et al, 1998); 4.1-Spec/Act and Ank-Spec/Act (Bennett and Baines, 2001). Scrib, which is also localized to BLJ, is not shown since we found that its loss does not cause invasion as defined in this work.…”
Section: Spatio-temporal Expression Of Fas2 Predicts Epithelial Invassupporting
confidence: 41%
See 1 more Smart Citation
“…The Fas2 tumor invasion and blocked BC migration phenotypes indicate that Fas2 is both necessary and sufficient to inhibit invasion, and that its pattern of expression predicts epithelial invasion. (Goodman et al, 1997); Dlg-4.1 (Lue et al, 1996); Nrg-Ank (Hortsch et al, 1998); 4.1-Spec/Act and Ank-Spec/Act (Bennett and Baines, 2001). Scrib, which is also localized to BLJ, is not shown since we found that its loss does not cause invasion as defined in this work.…”
Section: Spatio-temporal Expression Of Fas2 Predicts Epithelial Invassupporting
confidence: 41%
“…Second, Fas2 directly binds Dlg (Goodman et al, 1997). Third, molecular interactions between Nrg, Ankyrin, and Spectrin (Dubreuil et al, 1996;Hortsch et al, 1998) suggest a manner for Nrg to be linked to Fas2-Dlg through membrane protein 4.1 (Fig. 1B).…”
Section: Fas2 Dlg Lgl and Nrg Function Together To Suppress Invasionmentioning
confidence: 99%
“…The Schneider-2 (S2) cell line, which can express transfected genes, has revealed molecular mechanisms of cell adhesion [Hortsch and Bieber, 1991], much as Xenopus oocytes have done for ion channel function. Drosophila Neuroglian, whose human counterpart, L1 cell adhesion molecule (L1CAM/Nrg), is defective in a complex set of MR disorders [Weller and Gartner, 2001], controls axon pathfinding by regulating adhesive interactions between neurons [Hall and Bieber, 1997;Hortsch et al, 1998]. S2 cells expressing mutant forms of Neuroglian could be used to screen for drugs that restore cell adhesion.…”
Section: Prospects For Drug Discovery and Developmentmentioning
confidence: 99%
“…These results suggested that sodium channel ␤ subunits function as CAMs. CAMs of the L1 family also bind directly to cytoskeletal elements such as ankyrin (12,13,(15)(16)(17). Sodium channels have been shown to colocalize with ankyrin G and spectrin at axon initial segments and nodes of Ranvier, and there is some evidence to show that sodium channels bind ankyrin directly in vitro (18 -22).…”
mentioning
confidence: 99%
“…Ankyrins associate via their membrane binding domains with several ion channels and cell adhesion molecules of the L1 family (12)(13)(14)(15)(16)(17). The membrane binding domain of ankyrin contains four subdomains that are each composed of six ankyrin repeats (24).…”
mentioning
confidence: 99%